2018
DOI: 10.2147/ott.s175825
|View full text |Cite
|
Sign up to set email alerts
|

The clinical feasibility of flexible bronchoscopy interventional therapy in patients with central airway stenosis and respiratory failure caused by malignancy

Abstract: ObjectiveThe aim of this study was to investigate the clinical effects and feasibility of using flexible bronchoscopy intervention in cases of malignancy that causes central airway stenosis and respiratory failure.MethodsThe clinical data of patients who were admitted to the Department of Respiratory Medicine at the First Affiliated Hospital of Nanjing Medical University and underwent treatment of a malignant tumor with central airway stenosis and respiratory failure by flexible bronchos-copy from February 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Similar to the study reported by Ong, this study showed that patients with a high ECOG PS score [ 3 , 4 ] had a worse prognosis than patients with a low ECOG PS score [0–2] (the mean survival time was 3.85 months and 12.35 months, resp., P =0.004), indicating that patients with good PS might survive from stent implantation to prolong survival and improve oxygenation [ 19 ]. Stent placement has been proven to prevent acute asphyxia, reduce the patient's fear of sudden death, and provide patients with enough time to receive additional treatments, such as chemotherapy, radiotherapy, and palliative care [ 20 ]. Indications of airway stent implantation should be determined carefully for patients with poor PS.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the study reported by Ong, this study showed that patients with a high ECOG PS score [ 3 , 4 ] had a worse prognosis than patients with a low ECOG PS score [0–2] (the mean survival time was 3.85 months and 12.35 months, resp., P =0.004), indicating that patients with good PS might survive from stent implantation to prolong survival and improve oxygenation [ 19 ]. Stent placement has been proven to prevent acute asphyxia, reduce the patient's fear of sudden death, and provide patients with enough time to receive additional treatments, such as chemotherapy, radiotherapy, and palliative care [ 20 ]. Indications of airway stent implantation should be determined carefully for patients with poor PS.…”
Section: Discussionmentioning
confidence: 99%
“…For balloon dilation, Quantum maverick balloon catheter (Boston Scientific Corporation) was positioned within the stenotic area of the airway under flexible bronchoscopy visualization. The diameter of the balloon and expansion pressure were gradually increased depending on the diameter and length of the airway stenosis 10 . During the treatment, the balloon was inflated for 30–120 s with the expansion pressure 3–8 atm (balloon diameter: 3–5 mm) to dilate the airway.…”
Section: Methodsmentioning
confidence: 99%
“…Then carbon dioxide (CO 2 ) cryotherapy was undertaken in an attempt to ablate the residual granulation tissue and minimize recurrence of granulation tissue or scarring. For CO 2 cryotherapy, a cryo‐probe of 1.9 mm diameter (Erbokryo CA; Erbe) with CO 2 as cryogen was applied on the residual granulation tissue for 30 to 60 s, and these steps were repeated as required 9,10 . Sometimes, a biopsy forceps failed to removal of the lesion, because granulation, mucosal trauma, and multifactorial inflammation‐fibrosis cycle can lead to cicatrization 11 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Central airway obstruction (CAO) caused by intraluminal spherical masses is relatively rare and can be caused by multiple benign or malignant lesions that are easily misdiagnosed or missed. Due to the specific lesion site, many patients have urgent, critical symptoms at the time of treatment, and the disease progresses so quickly that the patients are prone to asphyxia; therefore, substantial attention should be paid to these lesions [1]. Intraluminal central airway masses vary in shape; most are irregular, but spheroid masses are occasionally encountered.…”
Section: Introductionmentioning
confidence: 99%